Determination of the Sterilization Dose of Gamma-Ray Irradiation for Polyvinyl Alcohol-Collagen-Chitosan Composite Membrane as a Material for Periodontal Regenerative Surgery - Susanto, Agus; Komara, Ira; Beatrix, Maria Theresia; Lukitowati, Fajar; Amaliya, Amaliya; Hendiani, Ina; Miranda, Aldilla (European Journal of Dentistry, 2023)
Objective Membrane sterility is very necessary considering its function as an implant material. Therefore, this research aims to determine the dose of gamma-ray irradiation for the sterilization of polyvinyl alcohol (PVA)–collagen–chitosan composite membranes used as regenerative surgery materials.Materials and Methods A total of 100 pieces of the composite membranes were prepared in a size of 2.0 × 1.5 cm by mixing 7.5% PVA, 3% collagen, and 2% chitosan using the film casting method in three batches. Furthermore, the bioburden test was performed to determine the initial microbial count in the sample by following ISO 11737-1. The results were used to ascertain the dose of gamma-ray irradiation on the sample according to ISO 11137-2. The dose verification test was then performed at the sterility assurance level 10−6.Results The average result of the bioburden test from three batches was 6.6 colony forming unit; hence, the verification dose was 4.8 kGy. In the verification dose test, since there was only one contaminated sample, the sterility dose test was continued.Conclusion The sterile gamma-ray irradiation dose for PVA–collagen–chitosan composite membrane was 17.1 kGy.
Keywords: PVA–collagen–chitosan; sterilization; gamma-ray irradiation